Analisa Pragmatik: Deiksis dalam Putusan Perkara Pidana Korupsi - Prosawita Ririh Kusumasari (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study analyzes the pragmatic elements used in the legal texis issued by Pengadilan Tinggi DKI Jakarta. This study aims to determine how the selection and use of deixis in corruption case decisions at the Jakarta high court. It referred to by the speaker and influenced by the meaning of the conversation. Data analysis was conducted by serving the text of the verdict on corruption cases issued at the Jakarta high court for 8 weeks. It was concluded that four types of deixis were used. They are place deixis, discourse deixis, first person, and demonstrative deixis